2020
DOI: 10.1186/s13073-020-00771-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a nonsense mutation located in the complex KIV-2 copy number variation region of apolipoprotein(a) in 10,910 individuals

Abstract: Background The concentrations of the highly atherogenic lipoprotein(a) [Lp(a)] are mainly genetically determined by the LPA gene locus. However, up to 70% of the coding sequence is located in the complex so-called kringle IV type 2 (KIV-2) copy number variation, a region hardly accessible by common genotyping and sequencing technologies. Despite its size, little is known about genetic variants in this complex region. The R21X variant is a functional variant located in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 64 publications
(159 reference statements)
1
37
0
Order By: Relevance
“…1,13 In addition, specific SNP haplotypes associate with Lp(a) concentrations that can be much lower or much higher than what would be expected from the sole size of the isoforms. 11,12 Some examples of such variants have been reported, [14][15][16] but many more probably exist. Genome-wide association studies (GWAS) have identified hundreds of variants associated with Lp(a) levels.…”
Section: P(a) (Lipoprotein [A]mentioning
confidence: 99%
“…1,13 In addition, specific SNP haplotypes associate with Lp(a) concentrations that can be much lower or much higher than what would be expected from the sole size of the isoforms. 11,12 Some examples of such variants have been reported, [14][15][16] but many more probably exist. Genome-wide association studies (GWAS) have identified hundreds of variants associated with Lp(a) levels.…”
Section: P(a) (Lipoprotein [A]mentioning
confidence: 99%
“…3). Stepwise conditional analyses within this framework identified an allelic series including 18 protein-altering variants and 3 variants in the 5’ UTR of LPA that each appeared likely to causally influence Lp(a) levels (based on achieving top or near-top association strengths in successive steps of analysis); 2 additional protein-truncating variants within KIV-2 exons had effects mostly masked by linkage disequilibrium with a canonical splice site variant 64 (Supplementary Table 3 and Supplementary Note). Second, we created an intuitive model that accurately predicted Lp(a) as a sum of allelic contributions determined by KIV-2 length and the combination of alleles of the 23 likely-causal LPA SNP and indel variants carried on each haplotype.…”
Section: Methodsmentioning
confidence: 99%
“…3). Stepwise conditional analyses within this framework identified an allelic series including 18 protein-altering variants and 3 variants in the 5' UTR of LPA that each appeared likely to causally influence Lp(a) levels (based on achieving top or near-top association strengths in successive steps of analysis); 2 additional protein-truncating variants within KIV-2 exons had effects mostly masked by linkage disequilibrium with a canonical splice site variant 64 (Supplementary Table 3 We compared the above model of Lp(a) to two simpler models corresponding to standard analyses: a model predicting Lp(a) from KIV-2 length alone (used in Fig. 2b) and a linear model a change in the log-ratio of observed vs. predicted Lp(a); if so, we exponentiated this change (and its 95% CI) and subtracted 1 to obtain non-log-scale changes in Lp(a).…”
Section: Logistic Regression Analyses Of Vntr Associations With Disease Outcomesmentioning
confidence: 99%
“…It is a likely causal SNP resulting in a nonsense mutation, which leads to a truncated protein that is rapidly degraded (Parson et al 2004). We recently developed a highly sensitive allele-specific qPCR assay and genotyped R21X in 10,910 individuals from three populations and showed that R21X carriers have significantly lower (À11.7 mg/dL) mean Lp(a) concentrations (Di Maio et al 2020). A study by Morgan and colleagues investigated two very rare variants, R990Q (rs41259144) located in the KIV type 4 and R1771C (rs139145675) located in the kringle V which were present in four null Lp(a) individuals.…”
mentioning
confidence: 99%
“…Later approaches that investigated LPA variants on the DNA level either by the number of KIV repeats identified by pulsed-field gel electrophoresis or by the sum of KIV repeats of the two alleles by quantitative PCR or by the investigation of SNPs that are associated with high Lp(a) concentrations revealed the same finding (Clarke et al 2009;Kamstrup et al 2009;Kraft et al 1996). On the other hand, genetic variants that are associated with low Lp(a) concentrations are obviously protective from CVD (Coassin et al 2017;Di Maio et al 2020;Lim et al 2014). These strong associations make Lp(a) probably the most important genetic risk factor for CVD if we keep in mind the high frequency of small apo(a) isoforms or variants which go along with high Lp(a) concentrations in the population (Kronenberg 2016b).…”
mentioning
confidence: 99%